Effect of long-term administration of antidepressants on the lipid composition of brain plasma membranes - Fisar, Z; Anders, M; Tvrzická, E; Stanková, B (General physiology and biophysics, 2005)
The connection between changes in lipid pattern in brain plasma membranes and long-term administration of therapeutically effective doses of antidepressants has not been sufficiently demonstrated so far. Therefore, we analyzed effect of antidepressants that differ in pharmacological selectivity on membrane lipid composition in the rat brain tissue. Laboratory rats were given desipramine, maprotiline, citalopram, moclobemide or lithium for a 4-week period. We observed a significant decrease in phosphatidylethanolamine representation after administration of maprotiline, citalopram and moclobemide when compared with controls. Membrane cholesterol content was decreased after desipramine administration and increased after citalopram or lithium treatment. Electroneutral phospholipids were decreased after the administration of all tested antidepressants except for desipramine. Decrease in phosphatidylserine was found following long-term administration of maprotiline or desipramine; relative representation of phosphatidylinositol was reduced after lithium treatment. Statistically significant negative correlation between cholesterol and electroneutral phospholipids was discovered. Membrane microviscosity evaluated by fluorescence anisotropy of membrane probes was only slightly decreased after desipramine and increased after citalopram administration. Hypothesis was supported that changes in brain neurotransmission produced by antidepressants could be, at least partially, associated with adaptive changes in membrane cholesterol and phospholipids.
Keywords: mozek; antidepresiva; zvířata; Brain; Rats; Adaptation, Physiological; Membrane Lipids; Animals; Rats, Wistar; Antidepressive Agents; potkani Wistar; Phospholipids; fyziologická adaptace; Time Factors; fosfolipidy; krysa rodu Rattus; časové faktory; membránové lipidy